THERMAL-ANALYSIS OF COORDINATION-COMPOUNDS .1. THERMODECOMPOSITION OF NICKEL(II) TRIPHENYLPHOSPHINE COMPLEXES WITH HALIDES, NITRATE, AND THIOCYANATE - Barbieri, R. S.; Rocha, J. C.; Dasilva, E. G. (Elsevier B.V., 1994)
The compounds [NiX2(PPh3)2] (where X is Cl-, Br-, I-, NO-, NCS-; and PPh3 is triphenylphosphine) were prepared and characterized by infrared and atomic absorption spectroscopies and by carbon and hydrogen analyses. Simultaneous thermogravimetric (TG) and derivative thermogravimetric (DTG) curves of these complexes were recorded in air. The decrease in mass observed indicates conversion of the complexes to oxides. The thermal decomposition of the halogen and nitrate complexes occurred in a number of steps; the thiocyanate complex decomposed in a single step.